Thymic T cells are driven to expand upon interaction with self-class II major histocompatibility complex gene products on accessory cells. - Rock, K L (1984)
Murine thymocytes induce the monokine interleukin 1 upon in vitro coculture with a radioresistant Ia-bearing accessory cell [murine Ia molecule is a class II major histocompatibility complex (MHC) antigen]. The generation of interleukin 1 is critically dependent on the function of I-region gene products on accessory cells. The induced interleukin 1 appears to allow the activation and proliferation of self-MHC-specific thymocytes. Thus, in the absence of added exogenous factors, there is an Ia-dependent thymocyte proliferation. This selective activation of thymocytes is observed with both mature and immature thymic T cells. This in vitro response results in the selective amplification of developing T cells with self-MHC specificity and could be of importance to the in vivo commitment of T cells to MHC determinants that occurs in the thymus.